2008
DOI: 10.1097/hco.0b013e3282fbf756
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular genetics of the short QT syndrome

Abstract: The short QT syndrome is clinically associated with atrial fibrillation, syncope and sudden cardiac death. A shortened QT interval (QTc <360 ms) and reduced ventricular refractory period together with an increased dispersion of repolarization constitute the potential substrate for reentry and life-threatening ventricular tachyarrhythmia. To date, gain-of-function mutations in KCNH2, KCNQ1, KCNJ2, encoding potassium channels and loss-of-function mutations in CACNA1C and CACNB2b, encoding L-type calcium channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 48 publications
0
41
0
3
Order By: Relevance
“…death (Schimpf et al 2008), and reduced HRV is also a known risk factor for cardiovascular events (Tsuji et al 1996). Whether a decrease from high doses of stimulants can have enduring effects on cardiac sympathetic function via altered striatal DAT and whether a dose reduction or discontinuation can possibly affect the QT interval may be worthy of further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…death (Schimpf et al 2008), and reduced HRV is also a known risk factor for cardiovascular events (Tsuji et al 1996). Whether a decrease from high doses of stimulants can have enduring effects on cardiac sympathetic function via altered striatal DAT and whether a dose reduction or discontinuation can possibly affect the QT interval may be worthy of further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Likewise, little is known about the significance of acquired, e.g., drug-induced shortening of QTc and therapeutic consequences are uncertain. 23,27,28 Primidone and rufinamide can both shorten QTc, 29,30 but these drugs were not used in our patients. Although the use of carbamazepine could have influenced our results, this drug is associated with bradyarrhythmias and has only minor effects on QT intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Shortening of QT is substantially mediated by circulating catecholamines and can be enhanced by hyperkalemia and acidosis. 23,27,28,33 All these conditions occur particularly during or shortly after GTCS. 18,19,34 Furthermore, chronic epilepsy patients display altered autonomic function with a presumably increased sympathetic tone and enhanced QT dispersion (spatial heterogeneity of cardiac repolarization), which are both independent predictors of cardiac mortality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, reggae (reg) mutants have a kcnh2 gain-of-function mutation leading to accelerated repolarization and, thus, can be considered a model for human short QT syndrome . Interestingly, reg mutants present with paroxysmal atrial fibrillation, a condition that has been found in human short QT syndrome (Schimpf et al, 2008). Slow mo (smo) is a mutant that is characterized by bradycardia (a slow heart rate).…”
Section: Primer Arrhythmiasmentioning
confidence: 99%